2017
DOI: 10.1038/s41467-017-00713-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping of otoliths drives vestibular behaviours in larval zebrafish

Abstract: The vestibular system, which detects gravity and motion, is crucial to survival, but the neural circuits processing vestibular information remain incompletely characterised. In part, this is because the movement needed to stimulate the vestibular system hampers traditional neuroscientific methods. Optical trapping uses focussed light to apply forces to targeted objects, typically ranging from nanometres to a few microns across. In principle, optical trapping of the otoliths (ear stones) could produce fictive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 29 publications
5
90
0
Order By: Relevance
“…Recording of the brain activity started 30s before the first stimulus onset and stopped after the return to white from the last loom of each block, resulting in three separated acquisitions. To image the larva and record its tail movements, a 4x 0.1NA Olympus microscope objective (PLN 4X) was placed below the sample chamber 61 , coupled with a tube lens projecting the image onto a Basler acA1920 camera, recording at 30 fps. At the end of each experiment, a single high-definition scan of non-binned images was recorded with 100ms exposure time and 2µm increments to be used for the registration of the brain of each fish (see below).…”
Section: Stimulus Train For Behavioural Experimentsmentioning
confidence: 99%
“…Recording of the brain activity started 30s before the first stimulus onset and stopped after the return to white from the last loom of each block, resulting in three separated acquisitions. To image the larva and record its tail movements, a 4x 0.1NA Olympus microscope objective (PLN 4X) was placed below the sample chamber 61 , coupled with a tube lens projecting the image onto a Basler acA1920 camera, recording at 30 fps. At the end of each experiment, a single high-definition scan of non-binned images was recorded with 100ms exposure time and 2µm increments to be used for the registration of the brain of each fish (see below).…”
Section: Stimulus Train For Behavioural Experimentsmentioning
confidence: 99%
“…Beyond this continuous stimulation protocol, the setup allows one to examine the whole-brain response to vestibular step-stimulation in the form of fast transient angular changes followed by periods of fixed angular position ( Fig. 3 An alternative approach to deliver vestibular cues to head-fixed larvae has recently been demonstrated, which consists of directly moving utricular otoliths using optical tweezers 11 . Although such manipulations do evoke small compensatory motor behaviors 11 , it is difficult to calibrate, which precludes the delivering of well-controlled and reproducible physiological stimuli.…”
Section: (67 Words)mentioning
confidence: 99%
“…3 An alternative approach to deliver vestibular cues to head-fixed larvae has recently been demonstrated, which consists of directly moving utricular otoliths using optical tweezers 11 . Although such manipulations do evoke small compensatory motor behaviors 11 , it is difficult to calibrate, which precludes the delivering of well-controlled and reproducible physiological stimuli. A complementary avenue to virtual reality systems may also be provided by functional recording in freely swimming fish, as was recently proposed 7,13 .…”
Section: (67 Words)mentioning
confidence: 99%
“…demonstrated manipulation of injected nanoparticles and bacteria and endogenous erythrocytes and macrophages in living zebrafish larvae . Manipulation of otoliths with sizes up to 55 microns in living zebrafish larvae was reported by Favre–Bulle et al …”
Section: Measurements In Complex Mediamentioning
confidence: 77%
“…Johansen et al demonstrated manipulation of injected nanoparticles and bacteria and endogenous erythrocytes and macrophages in living zebrafish larvae. [209] Manipulation of otoliths with sizes up to 55 microns in living zebrafish larvae was reported by Favre-Bulle et al [210] In vivo optical manipulation of red blood cells was reported by Zhong et al in mice. [211][212][213] Optical tweezers were used to perform microsurgery to clear blocked capillaries in blood vessels present in mouse ears.…”
Section: In Vivomentioning
confidence: 99%